(untitled) (Research, Society and Development, 2022)
Objective: To identify the main causes for devolution of requests via SISREG from UBS 4 of Recanto das Emas, from January to December 2021. Methodology: This is a cross-sectional descriptive study with a quantitative approach. Results: The main cause of devolutions was incomplete clinical information (62%). Other causes were incorrect exam or specialty (33%), incorrect/incomplete patient registration (4%), and patient can be managed in PHC (1%). Conclusion: The main causes of devolutions of request via SISREG from UBS 4 of Recanto das Emas are directly related to health processes, and are able to interventions in order to reduce access barriers and patient waiting time, leading to a SUS more effective, optimizing patients’ access to specialized services and complementary exams, valuing the principles of Universality, Equity and Integrality.